Mixing efficiency on plant cell growth and proteinase production in a stirred tank reactor - Raposo, Sara (2014)
Mixing efficiency is one of the most significant factors in bioprocess productivity. The major role of agitation is to improve broth homogenization, mass and heat transfer inside the bioreactors.